Intra‐Alpine Islands: Population genomic inference reveals high degree of isolation between freshwater spring habitats. (16th December 2021) - Blattner, Lucas; Lucek, Kay; Beck, Nathanael; Berner, Daniel; von Fumetti, Stefanie
Abstract: Aim: Alpine spring ecosystems have long been considered as highly isolated, island‐like habitats. This presumption, however, is insufficiently supported empirically and conclusions about spring isolation have been based on indirect evidence. Therefore, we investigated the population genomic structure of Partnunia steinmanni Walter, 1906, a strictly spring‐dwelling water mite (Hydrachnidia) species, to shed light on the degree of interconnection among freshwater spring habitats. Location: Protected areas across the Alps, Central Europe. Methods: Partnunia steinmanni populations were sampled by hand‐net from 12 springs. Population genomic structure was inferred with 2263 polymorphic restriction site‐associated DNA (RADseq) loci of 256 individuals. We assessed genomic admixture, the phylogenetic relationship, isolation by distance, contemporary migration, effective population sizes, and genetic diversity among individuals from different springs. Results: We observed strong genetic differentiation between individuals from different springs. Water mites from each spring qualified as well‐delimited distinct populations with only little intra‐spring migration, even when these were located in close geographic proximity. Furthermore, we found subtle shared genetic structure among springs within the same area, and a southwestern genotype associated with the Rhône catchment that extended into eastern populations. Effective population size estimates and standing genetic variation within springs were generally low. Main conclusions: Our findings indicate strong insularity of freshwater springs and headwater areas, likely caused by intra‐alpine Pleistocene isolation and limited dispersal abilities of strictly spring‐bound species like P . steinmanni . Our results support the concept of spring habitat isolation and highlight the importance of alpine protected areas to conserve springs as substantial components of freshwater biodiversity.